The Effect of Velvet Antler Proteins on Cardiac Microvascular Endothelial Cells Challenged with Ischemia-Hypoxia - Xiang Xiao; Shuqiang Xu; Lin Li; Min Mao; Jinping Wang; Yanjun Li; Ziwei Wang; Fei Ye; Li Huang (Frontiers Media S.A., 2017)
Velvet antler (VA) is a precious traditional Chinese medicine that is capable of repeated regeneration. Based on the Chinese medicine theory of coordination the heart and kidneys, VA has been employed to treat heart diseases, including ischemic heart disease, heart failure, and arrhythmia. We examined the effects of VA proteins on primary cardiac microvascular endothelial cells (CMECs) that were subjected to ischemia-hypoxia (IH) to investigate their effects on and mechanism of action in the treatment of ischemic heart disease. Velvet antler proteins (VA-pro) were extracted with water as the solvent, the ultrasonic wave method, and freeze-drying technology; then it was analyzed by Nano LC-MS/MS. In addition, the role of VA-pro in cell viability, proliferation, apoptosis, and mitochondrial membrane potential (MMP) were evaluated by the MTS assay, the EdU assay, the Annexin V-FITC/PI double-staining assay, and the JC-1 assay, respectively. Cell migration were evaluated by the scratch assay and the Transwell assay. The expression of apoptosis-associate proteins, Akt and p-Akt, and tube formation in Matrigel of CMECs were also detected. In total, 386 VA-pro were identified. Our results showed that IH significantly reduced the viability of the CMECs (P < 0.001) and suppressed copies of DNA to hold back CMEC proliferation (P < 0.001). The OD of control group was 1.81 ± 0.08 and IH group OD was 1.25 ± 0.03. After suffering with IH for 46 h, CMECs were 75% less likely to migrate (P < 0.001), and its tubule formation ability and MMP were also decreased (P < 0.001). VA-pro treatment resulted in an improvement in CMECs' viability and proliferation (P < 0.001). Such as, the OD of 0.5, 1, and 2 mg/ml rose to 1.56 ± 0.5, 1.74 ± 0.1 and 1.65 ± 0.1, respectively. Similarly, CMECs' migration (for the scratch assay P < 0.001, for the Transwell assay P < 0.05) and tubule formation (P < 0.05) ability were better after treated with VA-pro. At the same time, the stability of MMP was retained preferably (P < 0.001). 50% apoptosis was induced after CMECs were cultured in IH conditions (P < 0.001), while VA-pro decreased the number of apoptotic cells (P < 0.001). All above results showed that 1 mg/ml VA-pro produced maximum results. Furthermore, the expression of pro-apoptosis proteins was higher, but the expression of anti-apoptosis proteins was lower in the IH group (P < 0.05); VA-pro reversed these changes (P < 0.001). These findings suggest that VA-pro ameliorate CMEC injuries induced by IH via regulating the PI3K/Akt signaling pathway.